2010
DOI: 10.1007/s10620-010-1284-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Physician Supplies with Colon Cancer Care in Ontario and California, 1996 to 2006

Abstract: These colon cancer care findings support the theory that while personal economic resources are more predictive in America, community-level resources such as physician supplies are more predictive of health care access and effectiveness in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…This finding is in line with current literature: A study conducted within Adelaide (Australia) found similar distribution patterns: 16% of residents were reported to live in an area of GP shortage within Adelaide boundaries [26]. An unbalanced distribution of physicians was further reported for Auckland (New Zealand) [27] and Toronto (Canada), where the authors reported a range of 6.18–12.42 GPs per 10^4 residents for the city districts of Toronto [28]. In our study, the number of FTE per 10^4 residents ranged between 1.80–43.98 and therefore variation was higher compared to the Canadian study.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is in line with current literature: A study conducted within Adelaide (Australia) found similar distribution patterns: 16% of residents were reported to live in an area of GP shortage within Adelaide boundaries [26]. An unbalanced distribution of physicians was further reported for Auckland (New Zealand) [27] and Toronto (Canada), where the authors reported a range of 6.18–12.42 GPs per 10^4 residents for the city districts of Toronto [28]. In our study, the number of FTE per 10^4 residents ranged between 1.80–43.98 and therefore variation was higher compared to the Canadian study.…”
Section: Discussionsupporting
confidence: 86%
“…We think probably not for the following reasons. Analyses of the same Ontario-California database observed significant primary care physician-cancer care effects that were not moderated by income in Ontario, but no such independent effects of primary care in California (Gorey et al, 2009a(Gorey et al, , 2009b. Moreover, consistent with other analysts (McGrail et al, 2009), we found that after income or insurance status are accounted for, primary care itself seems to explain very little of the health inequalities in Canada or the United States.…”
Section: Potential Study Limitationssupporting
confidence: 86%
“…Three thousand, three hundred women diagnosed with colon cancer between 1996 and 2000 were randomly selected from the California Cancer Registry and joined to the 2000 census by census tracts [ 17 - 20 ]. The original sample was then stratified by socioeconomic status: high poverty neighborhoods where 30% or more of the households were poor, mid-poverty neighborhoods where 5% to 29% were poor or low poverty neighborhoods where the prevalence of poverty was less than 5% [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%